Ensino-aprendizagem das ciências naturais em básica primária, com pessoas jovens e adultas, na Colombia - Gomez, Maria Luz Builes (2006)
This work has as objetive to analyze some aspects of the teaching-learning of the natural sciences, in basic primary classes, with young and adult students. To get to know the existent official curricular dispositions in Colombia, the why and the what for, the what and the how of the teaching-learning of the natural sciences in basic primary classes, with young and adult students, we ve interviewed 10 teachers who act in primary basic education, of young and adult students, in official and private educational institutions, in the department of Antioquia-Colombia. The collected data were classified around the central idea of didactics-currículum as analytical axis. From this axis we ve carried out a thematic analysis, based upon authors like Astolfi and Develay, Giordan, Bronckart, Gimeno Sacristan, Apple, Chassot, Gil and Pessoa, Faundez, Mugrabi. The analysis of the data indicates us that in Colombia it does not exist an specific curricular policy for the teaching-learning of the natural sciences for young and adult students in primary basic education; and that the practices of teaching-learning of the natural sciences approach the traditional models, behaviorism and constructivism, prevailing the traditional pattern: scientific vision of the natural sciences, where they are considered as the only and true sciences; very wide study plans, of encyclopedic type, the same ones that exist for school boys and girls, which are out of context of the reality of young and adult students; fragmented contents of conceptual type; expositive classes; individual and limited evaluations almost exclusively to judge and to measure; limited time dedicated to the area; and poor resources available to the educational institutions. As an exploratory study, it does not suggest a general conclusion; however, it looks forward to contributing as a preliminary diagnosis for future actions